STRATEGI KOMUNIKASI CORPORATE SOCIAL RESPONSBLITY (CSR) PT. JASA RAHARJA CABANG RIAU DALAM MEMBINA KEMITRAAN UMKM KOTA PEKANBARU - Roza, Elisa; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Indonesian economy is increasingly aware that the development and growth of Micro, Small and Medium Enterprises (MSMEs) has an important role in a country's economy. In general, the UMKM sector plays an important role in creating jobs, encouraging economic growth and accelerating the process of income distribution through business opportunities. PT. Jasa Raharja Riau Branch as a BUMN company plays an active role in helping the growth of MSMEs in Pekanbaru City. This study aims to determine the CSR communication strategy carried out by PT. Jasa Raharja Riau Branch, namely the determination of communicators, audiences, messages, media and audience responses in an effort to foster MSME partnerships in Pekanbaru City.This research uses a qualitative method. The informants consisted of 6 people who were representatives of the company and the community. The technique of determining informants is done purposively, namely determining research informants who are considered masters and can be trusted to be sources of information. Data collection techniques were carried out observation, interviews and documentation. Data analysis techniques using interactive analysis models include three stages, namely data reduction, data presentation and conclusion drawing. The technique for checking the validity of the data is by trianggulation and extension of participation.The results showed that the communicator strategy was divided into two communicators in the socialization, namely the Head of PKBL as the main speaker. Whereas communicators on program communication and coordination on an ongoing basis are carried out IM by the PKBL Division. Audience strategy of PT. Jasa Raharja in the Riau branch is distinguished among the primary audience, namely all the MSMEs in Pekanbaru City. The message strategy starts with sending formal messages, compiling the main message core, namely efforts to alleviate economic problems through the improvement of MSMEs through CSR programs. The message used when socializing is informative, persuasive and with presentation techniques. The media used are formal letter media, websites, printed bulletins and communication from the mouth of the mouth.